Risk factors for suicidal ideation: study with nursing professionals (Research, Society and Development, 2023)
This study aims to analyze aspects of suicide risk among nursing professionals at the Hospital de Clínicas of the Federal University of Uberlândia (HC-UFU) /EBSERH. This is an observational, descriptive, cross-sectional study with a quantitative approach started in 2021, using a research database entitled “PATIENT SAFETY, SUICIDE AND VIOLENCE IN HEALTH SERVICES: INTERRELATIONS AND INTERVENTION PROPOSAL”, with the collection being carried out in 2020 with 226 professionals, 58 nurses and 166 technicians and nursing assistants. The results showed that the mean age was 41.5 years, the weekly workload was 36.0 hours and the time working in the nursing field was 17 years. And the fact that 30 (12.7%) of the participating professionals thought it would be better to have been dead in the last year, 18 (7.6%) had already thought about suicide, 2 people (0.8%) had already attempted suicide, 8 (3.4%) have already made a suicide attempt, and 13 (5.8%) are considered people at high risk for suicide, it deserves attention, since this situation affects the health of the worker, and consequently and possibly in the assistance provided. Knowing the factors that predispose a person, and so to speak, a class of workers, nursing, to attack their own lives is the first step to assess the need to structure work effectively in the prevention and promotion of an environment insurance for the professional and patient.